2007
DOI: 10.1111/j.1365-2621.2006.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the loss of tensile, barrier and appearance properties caused by plasticiser crystallisation in whey protein films

Abstract: Whey protein films plasticised with sucrose have excellent oxygen barrier properties and high gloss that are reduced with time as sucrose crystallises. Whey protein isolate (WPI) films plasticised with sucrose were stored in 53% relative humidity for up to 60 days. The oxygen permeability, tensile properties and gloss of the films were measured periodically following ASTM (American Society for Testing Materials) methodology. Changes in properties were compared with changes in WPI films plasticised with glycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
1
9
0
4
Order By: Relevance
“…In addition, these edible films were reported not to modify the sensory attributes of the coated good or its aspect, while providing some health benefits for the consumer [5]. A number of authors have also reported the good barrier properties of whey protein-based coating on paper [6,7], but also on plastic substrates [8][9][10][11][12]. As yet, none of these academic studies has been routed to the industry and the present study demonstrates the scale-up ability.…”
Section: Introductionmentioning
confidence: 59%
“…In addition, these edible films were reported not to modify the sensory attributes of the coated good or its aspect, while providing some health benefits for the consumer [5]. A number of authors have also reported the good barrier properties of whey protein-based coating on paper [6,7], but also on plastic substrates [8][9][10][11][12]. As yet, none of these academic studies has been routed to the industry and the present study demonstrates the scale-up ability.…”
Section: Introductionmentioning
confidence: 59%
“…Overall results showed that mechanical properties of all film samples were enhanced during extended storage period ([7 days). Improved mechanical properties of WPI films have been reported during aging (Anker et al 2001;Dangaran and Krochta 2007) and heat curing (Amin and Ustunol 2007;Miller et al 1997). The enhanced cohesive forces in polymer films induced by gradual molecular rearrangement were hypothesized to be responsible for the stronger and less extensible film.…”
Section: Changes In Properties Of Spiced Film During Storagementioning
confidence: 99%
“…The use of whey proteins for film formulation has been extensively reviewed, since these proteins are both edible and biodegradable, favor the reuse of cheese making effluents, and also have interesting mechanical and barrier properties (Javanmard, 2009;Ramos, Reinas, Silva, Fernandes, Cerqueira, & Pereira, 2013). Whey protein-based films mostly include food materials, which can change over time causing loss of protective functions and affecting the appearance of the covered food (Dangaran & Krochta, 2007). Therefore, the effect of storage on some film properties has been rather unexplored in most research papers.…”
Section: Introductionmentioning
confidence: 99%